Surface structure of mass-selected niobium oxide nanoclusters on Au(111). (31st August 2021) - Wang, Jason; Ma, Yilin; Mahapatra, Mausumi; Kang, Jindong; Senanayake, Sanjaya D; Tong, Xiao; Stacchiola, Dario J; White, Michael G
Abstract: The structures formed by the deposition of mass-selected niobium oxide clusters, Nb3 O y ( y  = 5, 6, 7), onto Au(111) were studied by scanning tunneling microscopy. The as-deposited Nb3 O7 clusters assemble into large dendritic structures that grow on the terraces as well as extend from the top and bottom of step edges. The Nb3 O6 cluster also forms dendritic assemblies but they are generally much smaller in size. The assemblies are composed of smaller discrete structures (<1 nm) which are likely to be single clusters. The dendritic assemblies for both the Nb3 O7 and Nb3 O6 clusters have fractal dimensions of about 1.7 which is very close to that expected for simple diffusion limited aggregation. Annealing the Nb3 O7, 6 /Au(111) surfaces up to 550 K results in changes in assembly sizes and increases in heights, while heating to 700 results in the disruption of the assemblies into smaller structures. By contrast, the as-deposited Nb3 O5 /Au(111) surface at RT exhibits compact cluster structures which become 3D nanoparticles when annealed above 550 K. Differences in the observed surface structures and thermal stability are attributed to differences in metal-oxygen stoichiometry which can influence cluster binding energies, mobility and inter-cluster interactions.